Part Time "Gardeners as "Nuclei of Sustainable Communities" - Ng Liang, Shing (2014)
We present success stories of "part time gardeners" in several states of Peninsular Malaya (Kedah, Perak, Kuala Lumpur, Selangor, Ncgeri Sembilan and Pahang) and Sarawak and examine their opportunities and challenges, with specific focus on organic farming or organic gardening. The gardeners involved come from a variety of background. The location of the gardens or farms also vary from outskirt of an expanding urban area to the campus of universitieL. The common theme behind this versatility is "sustainable community" -- how these active practitioners of gardening or farming may form the "nuclei" of "sustainable communities" that we have to develop in order to have a "livable environment" in the future at all. We examine the challenges they face and propose some solutions - which call for long term, coordinated, bottom-up and top-down efforts. Two of the main challenges are (1) lack of open and Lair market and price mechanisms, which prevented many "part time" and small scale producers from growing bigger in scale, and attracting more new investors and participanis, as commercial incentives are as important as "pure passion" to sustain a social enUeprise (2) access to water and management of the ecosystem. As solutions, (1) We examine examples like the Xinfadi farmers market in Beijing, China and its use of webtechnologies for updating prices (2) We analyse the functions of canals which played an important role in "sustainable communities" in management of the ecosystem before industrialization, and demonstrate its huge potential for a possible "paradigm shift" of urban development model -- from "modern concrete jungle" back to the livable sustainable canal centred communities". We also compare "part time gardeners" to "free software programmers" who gave us technologies like Android, who will he the main players in spreading farming knowledge in building sustainable communities. in abort, the experiences of these "part time gardeners" and lessons drawn from history provc that "there is hope" in building ",Future sustainable communities".